Validity and Reliability Test of the Procrastination Assessment Scale-Student Questionnaire Part 2 Indonesian Version Uji Validitas dan Realibilitas Kuesioner Procrastination Assessment Scale-Student Bagian 2 Versi Bahasa Indonesia - Azkiah, Wa Ode Nurul; Abdullah, Yenny; Tandirogang, Nataniel (Jurnal Medika : Karya Ilmiah Kesehatan, 2024)
Abstract Academic procrastination is the behavior of procrastinating or procrastinatingComplete academic assignments based on your own wishes. QuestionnaireProcrastination Assessment Scale-Student (PASS) is a questionnaire to find outstudent academic procrastination. This questionnaire consists of 2 parts, part 1 discussesprevalence of academic procrastination and part 2 discusses the reasons for procrastination. StudyThis aims to obtain the Indonesian version of the PASS questionnaire part 2valid and reliable. The type of research is cross sectional research. The questionnaire consists of26 question items distributed via Google form to 30 active students of the Study ProgramMulawarman University Medicine in January-February 2022. Carried outadaptation and translation of PASS part 2 into Indonesian, followed by validity testingcontent and construct validity tests using the Pearson correlation test and reliability testusing Cronbach's alpha value. The validity test results show that there are 2 items that are notvalid (r < 0.361) and the results of the reliability test show that the questionnaire is reliable with Cronbachalpha coefficient of 0.894 (α > 0.7). The research conclusion is that there are 2 items droppedin this questionnaire and the Indonesian version of PASS part 2 are valid and reliable for measuringreasons for academic procrastination of University Medical Study Program studentsMulawarman. Therefore, the Indonesian version of PASS part 2 can be usedto measure the reasons for students' academic procrastination.